The Role of Biomaterials as Angiogenic Modulators of Spinal Cord Injury: Mimetics of the Spinal Cord, Cell and Angiogenic Factor Delivery Agents - Luís A. Rocha; Luís A. Rocha; Luís A. Rocha; Rui A. Sousa; David. A. Learmonth; António J. Salgado; António J. Salgado (Frontiers Media S.A., 2018)
Spinal cord injury (SCI) represents an extremely debilitating condition for which no efficacious treatment is available. One of the main contributors to the inhospitable environment found in SCI is the vascular disruption that happens at the moment of injury that compromises the blood-spinal cord barrier (BSCB) and triggers a cascade of events that includes infiltration of inflammatory cells, ischemia and intraparenchymal hemorrhage. Due to the unsatisfactory nature of revascularization following SCI, restoring vascular perfusion and the BSCB seems an interesting way of modulating the lesion environment into a regenerative phenotype, with a potential increase in functional recovery. Certain biomaterials possess interesting features to enhance SCI therapies, and in fact have been applied as angiogenic promoters in other pathologies. The present mini-review intends to highlight the contribution that biomaterials could make in the development of novel therapeutic solutions able to restore proper vascularization and the BSCB.